Caracterização física, química, mineralógica e metalúrgica dos produtos granulados de minério de ferro - Eunirio Zanetti Fernandes (2008)
The main purpose of this thesis is the technological characterization of iron ores granulated products (lump ores), through of study of chemical and physical correlations, typologies, metallurgical behavior and mineralogy of eleven from Vales South System mines. In terms of granulometric distribution, the majors percentages are concentratedbetween fractions 31,50 to 12,50 mm. The most important chemical correlations are: alumina and loss of ignition; manganese an magnesium; calcium and magnesium; manganese and calcium, alumina and phosphorus and the main negative correlations are: iron total and silica; iron total and alumina; iron total and FeO; manganese and titanium. The average grades of zinc, sodium and potassium of eleven samples were very low. The compact and compact porous typologies are predominate, with hipogenic characteristics and porous, associated to canga, itabirites and proto ore typologies, derived from iron ores supergene alteration. The irons grades are higher in the compacttypologies and aluminas grades and loss of ignition are higher in the typologies associated to canga. The metallurgic indexes are correlated to alteration grade, percentage of typologies and main chemical variables. In mineralogical terms the granular and sinuous hematites present higher percentages in compact, compact porus and porous typologies, with an specific behavior relating to metallurgic indexes, while martite, lamellar hematite, goethite and gibbsite increase their percentages in porous, canga, itabiritc and proto ore typologies and their behavior is the same related to metallurgic indexes. The microcrystalline hematite and jacobsite are restricted to proto ore typology. The relative porosity increase from compact typology to porous, canga, itabiritic and proto ore typologies. The average sizes of porous are large in porous, cangas, itabiritics and proto ore typologies. The typologic evaluation could be used in preliminary metallurgic evaluation. The fine generated by tumbler assays were studied with objective to evaluate the effect of handing and transport of iron ores granulated products, has been determined the importance of granulometric, chemistry and mineralogic variables in aggregation of fine fractions.